Modulation of Oxidative Stress and Haematological Parameters by Peppermint and Lemongrass Essential Oils in Lactating Crossbred Cows (Indian Journal of Animal Production and Management, 2024)
This study evaluated the impact of dietary  supplementation with peppermint and lemongrass  essential oils (EOs) on various biochemical  parameters in lactating dairy cattle over 90 days.  The experiment was conducted at the Instructional  Dairy Farm, GBPUA&T, Pantnagar, Uttarakhand,  India, and involved 18 animals divided into three  groups. The control group (T0) animals received a  basal diet, while in T1 group animals, concentrate  was supplemented with 0.1% peppermint EO and  T2 groups with 0.1% lemongrass EO. Blood  samples were collected on day 0, and after 30, 60,  and 90 days for the study of hematological and  antioxidant parameters. Hematological parameters  viz. Hb, TEC, PCV, eosinophil, monocyte, platelets,  MCV, MCH, and MCHC, remained within normal  ranges across all groups, with no significant  differences observed. However, TLC and neutrophil  concentrations were significantly (P
Keywords: antioxidants; crossbred lactating cattle; hematology; lemongrass oil; peppermint oil